2023
DOI: 10.1186/s13046-023-02718-w
|View full text |Cite
|
Sign up to set email alerts
|

MiR-494 induces metabolic changes through G6pc targeting and modulates sorafenib response in hepatocellular carcinoma

Abstract: Background Metabolic reprogramming is a well-known marker of cancer, and it represents an early event during hepatocellular carcinoma (HCC) development. The recent approval of several molecular targeted agents has revolutionized the management of advanced HCC patients. Nevertheless, the lack of circulating biomarkers still affects patient stratification to tailored treatments. In this context, there is an urgent need for biomarkers to aid treatment choice and for novel and more effective therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Since two miR-10b inhibitors have been developed based on advances in nanotechnology (TTX-MC138 and RGLS5579), demonstrating an effective anticancer activity in preclinical models [50], this miRNA investigation holds promise both as a therapeutic target and a predictive biomarker. Finally, a study by our research group reported the association between high miR-494 serum levels and sorafenib resistance in HCC patients at baseline [68]. In addition, we underlined the relationship between miR-494 serum levels and genes involved in the metabolic reprogramming of cancer cells, pointing out the possibility that circulating levels of this miRNA might not only predict sorafenib response but also identify tumors with a deregulated metabolism that could benefit from combined TKI and antagomiR or metabolic interference strategies.…”
Section: Noncoding Rnas As Biomarkers Of Treatment Response In Hccmentioning
confidence: 77%
See 1 more Smart Citation
“…Since two miR-10b inhibitors have been developed based on advances in nanotechnology (TTX-MC138 and RGLS5579), demonstrating an effective anticancer activity in preclinical models [50], this miRNA investigation holds promise both as a therapeutic target and a predictive biomarker. Finally, a study by our research group reported the association between high miR-494 serum levels and sorafenib resistance in HCC patients at baseline [68]. In addition, we underlined the relationship between miR-494 serum levels and genes involved in the metabolic reprogramming of cancer cells, pointing out the possibility that circulating levels of this miRNA might not only predict sorafenib response but also identify tumors with a deregulated metabolism that could benefit from combined TKI and antagomiR or metabolic interference strategies.…”
Section: Noncoding Rnas As Biomarkers Of Treatment Response In Hccmentioning
confidence: 77%
“…We demonstrated that the miR-494/G6pc axis contributes to the metabolic plasticity of cancer cells, favoring the accumulation of glycogen and lipid droplets that are exploited in the case of critical metabolic conditions (e.g., glucose deprivation), giving an advantage to the uncontrolled proliferation of malignant cells. We also showed that the miR-494/G6pc axis promotes sorafenib resistance and proposed combining antagomiR-based treatments with sorafenib or 2-deoxyglucose (2-DG) for HCC patients who may develop sorafenib resistance and who are ineligible for immunotherapy [68]. An interesting study by Zhang et al [69] demonstrated the pivotal role of the miR-30a-5p/CLCF1 axis in modulating the metabolic shift toward the aerobic glycolysis of SR HepG2 cells and xenograft tumors.…”
Section: Noncoding Rnas Affect Sorafenib Response By Interfering With...mentioning
confidence: 93%
“…Towards this end, it has already been shown that miR-494 could play a critical role during imatinib treatment in resistant prostate cancer and CML leukemic stem cells [ 85 , 86 ]. Additionally, high expression of miR-494 was shown to be associated with the induction of sorafinib resistance in hepatocellular carcinoma [ 87 , 88 , 89 ]. Another study aiming to explore the ability of miR-494 and FGFR2 to regulate the cancer-initiating cell phenotype and the therapeutic efficacy of lapatinib in HER2-positive gastric cancer found that increased miR-494 expression was able to reduce lapatinib resistance in these cells [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the main way to acquire energy in cancer cells is aerobic glycolysis even under the condition of adequate oxygen. Accumulated evidence suggests there are numerous glucose metabolism-associated ncRNAs dysregulated in cancers resulting in mitochondrial dysfunction, abundant activation of key enzymes, altered isozyme profiles and dysregulated glucose metabolic signalling pathways [ 64 66 ]. Current progress in the role of ncRNAs in glucose metabolism has been summarized in Fig.…”
Section: Ncrnas Affect Cancer Progression Through Metabolic Reprogram...mentioning
confidence: 99%